Living with chronic headache: a qualitative study exploring goal management in chronic headache. Issue 25 (4th December 2018) - Ciere, Yvette; Visser, Annemieke; Jacobs, Bram; Padberg, Marielle; Lebbink, John; Sanderman, Robbert; Fleer, Joke
Abstract: Objectives: Effective goal management may potentially prevent or reduce disability in chronic pain. The aim of this study was to gain insight into the nature of goal management in the context of chronic headache (CH). Methods: Interviews with 20 patients were conducted, coded, and analyzed using a combined data-driven and theory-driven approach. The dual process model (DPM) was used as a theoretical framework for this study. Results: Participants used a combination of strategies to regain and maintain a balance between personal goals and resources available for goal pursuit. Furthermore, their retrospective reports indicated a development in strategy use of time. Three goal management phases were identified: (1) a "persistence phase, " characterized by the use of "resource-depleting" assimilative strategies to remain engaged in goals, (2) a "reorientation phase" in accommodative strategies were used to regain balance, and (3) a "balancing phase" in which a combination of "resource-depleting" and "resource-replenishing" assimilative strategies was used to maintain balance. Conclusions: Goal management is a dynamic process that may contribute to the development of, and recovery from, headache-related disability. Rehabilitation services offered to individuals with CH should target this process to promote optimal functioning. Implications for Rehabilitation: Individuals with chronic headache use assimilative and accommodative goal management strategies to be able to pursue personal goals despite the limitations of chronic headache. Before accommodating goals to the limitations of chronic headache, many patients go through a phase of persistence, characterized by the use of resource-depleting assimilative strategies. A reorientation phase, characterized by accommodation of goals to the limitations of chronic headache, allows patients to adopt a more balanced way of pursuing personal goals.